2023
DOI: 10.3390/ijerph20085537
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed-Method Examination of Emerging and Young Adult Cancer Caregivers’ Experiences during the COVID-19 Pandemic

Abstract: Advanced cancer caregivers in emerging and young adulthood (EYACs; ages 18–35) are an understudied yet vulnerable caregiving population. The COVID-19 pandemic created new challenges for advanced cancer caregivers but also created unique contexts from which caregivers sometimes benefited. To understand how the pandemic may have positively and negatively impacted their caregiving and bereavement experiences, we examined EYACs’ experiences of caring for and losing a parent with advanced cancer during the pandemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…As in other pandemic caregiver studies, inability to accompany patients to appointments and be included in important medical consultations negatively impacted caregiver perceived e cacy (23,24,26), and caused feelings of sadness, guilt and regret. These emotions related not only to their inability to offer emotional support, but also practical support in terms of keeping check on the care and treatment provided, with caregivers left feeling helpless and experiencing loss of control, particularly when mistakes or poor treatment occurred.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…As in other pandemic caregiver studies, inability to accompany patients to appointments and be included in important medical consultations negatively impacted caregiver perceived e cacy (23,24,26), and caused feelings of sadness, guilt and regret. These emotions related not only to their inability to offer emotional support, but also practical support in terms of keeping check on the care and treatment provided, with caregivers left feeling helpless and experiencing loss of control, particularly when mistakes or poor treatment occurred.…”
Section: Discussionmentioning
confidence: 88%
“…While some positive caregiver experiences have been observed relating to enhanced family-time and coping (22)(23)(24)(25), the small number of studies available have more commonly reported negative experiences amongst current (24)(25)(26) and bereaved (22,23) caregivers. These include reduced social support for family caregivers (22,24), detrimental impacts on caregiver wellbeing, quality of life and perceived e cacy (23)(24)(25)(26)(27) and concerns over the quality of care and treatment provided to the patient and the infection risks posed by COVID-19 (23,24). The need for families to have a clear understanding of their family member's condition and declining health, stay connected with them in the nal weeks/days of life and have the opportunity for nal contact before they died has also been described (27) .…”
Section: Introductionmentioning
confidence: 99%